2020
DOI: 10.1111/1471-0307.12690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray‐drying parameters on the solubility and the bulk density of camel milk powder: A response surface methodology approach

Abstract: Response surface methodology coupled with a Box–Behnken experimental design was used to investigate the effect of the air inlet drying temperature, the feed rate, and the fat content on the solubility and the bulk density of spray‐dried camel and cow milk powders. The response surface methodology analysis highlighted that milk fat content and feed rate were the most effective parameters affecting the solubility and the bulk density of cow and camel milk powders. Importantly, there was no significant interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…(2018) and Zouari, Mtibaa, et al. (2020). These authors reported that camel milk powders presented higher bulk densities than those observed for bovine milk powders.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…(2018) and Zouari, Mtibaa, et al. (2020). These authors reported that camel milk powders presented higher bulk densities than those observed for bovine milk powders.…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies on camel milk powder have been focused on its particle structure and surface composition (Zouari, Schuck et al., 2020), as well as its behavior during drying (Habtegebriel, Edward, Wawire, Sila, & Seifu, 2018; Zouari et al., 2019; Zouari, Mtibaa et al., 2020) and its physicochemical changes upon storage (Ho et al., 2019; Zouari, Briard‐Bion et al., 2020). However, none of these explained the practical conditions to use skimmed or whole‐fat camel milk powder in future applications.…”
Section: Introductionmentioning
confidence: 99%
“…The MLR and ANOVA were performed on each physical quality attribute as well as the yield. It was suggested that a good regression model should have R 2 no less than 80%, 37 and the p-value of model should be less than 0.05. The fitting results illustrated that the yield, hygroscopicity, and particle size distribution width could not be fitted well (i.e., R 2 The pareto charts of standardized effects on MC (Figure 1A) and SSA (Figure 1B) are shown.…”
Section: Identification Of Critical Process Parametersmentioning
confidence: 99%
“…Heat consumption during a constant drying rate remains constant, and increases during a period of a decreasing drying rate. At the final stage, starting with the mass fraction of moisture in the product, energy consumption increases many times [18][19][20]. This makes the spray drying process ineffective.…”
Section: аннотацияmentioning
confidence: 99%